STABILITAS EMOSI PELAKU PERNIKAHAN DINI DALAM MENDIDIK ANAK BALITA - Lu’ Luul Jannatunnaim (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2018)
The rate of early marriage from year to year continues to increase due to economic factors, family internal factors, and social factors. Most early marriages are still middle school / high school students who do not have good emotional stability and tend to do everything they want without thinking about the impact that will occur. Many of the early marriages have children, where in educating children they unconsciously apply permissive education patterns. The personal circumstances and attitudes of each child are different, making the task of educating hard to implement, and in?uencing the emotional state of parents. The results showed that the emotional stability of early marriages in educating children is not good, this is because early marriages are still easily in?uenced by negative emotions that can be seen from the emotional response shown. Excessive emotional response is not in accordance with the notion of emotional stability, namely a permanent emotional state, not easily changed, and the response shown is not excessive. In relieving negative emotions and resolving problems that occur, early marriages more often submit to the situation assuming that emotions will be lost if left unchecked, without any effort to fnd a way out or a method of solving the problem accordingly. Although early marriages do not have good emotional stability, some early marriages have been able to maintain their emotional stability by calming themselves down and solving problems that are sources of emotion.